Grænser for religion - Lüchau, Peter ca. 20. Jh. (Religionsvidenskabeligt tidsskrift, 2015)
Where and in what context Danes accept religion is dependent upon their attitudes toward the boundaries of religion. Dependent upon the theoretical point of departure, the boundary may be expected to be situated between religion in the public and the private sphere (secularization theory) or between religious exercise of authority and religious self-expression (individualization theory). To determine which theory may best explain the Danes' view concerning the acceptable place of religion in Denmark, data from the International Social Survey Programme 2008 ? Religion III questionnaire are utilised. The analysis shows that the boundary of religion is situated at the point of religious exercise of authority, and thus individualization theory best explains the limits of religion in Denmark. Furthermore, it can be shown that this boundary is part of the existing value-based cleavages among the Danes.